Sobre conhecimento factual e rastreamento da verdade - Chiodelli, Taís Regina (2023)
The aim of this work is to show the singularity as well as examine the plausibility of the Countdown Clock case of John Williams and Neil Sinhababu (2015), which is very little known in the field, as a counterexample to the Truth Tracking theory of Robert Nozick (1981) and its successor principles: the Sosa version of the defended security (2002) and the Pritchard versions of the defended security (2012), which he proposed in order to falsify them as anti-luck theories. For this, we will make an explanatory exposition of these epistemologies, elucidating the modal nature of the concept of truth tracking that share in their fundamental principles and show their reasonableness as epistemologies of the type, analyzing them in light of Gettier’s main cases. Next, we will present the case we call the Regressive Clock, we will explain how it is intended to falsify these epistemologies and we will analyze their legitimacy.